2017
DOI: 10.1371/journal.pgen.1006557
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-ABL1-TOR Signaling Modulates Cell Cycle Tuning to Control Terminal Appressorial Cell Differentiation

Abstract: The conserved target of rapamycin (TOR) pathway integrates growth and development with available nutrients, but how cellular glucose controls TOR function and signaling is poorly understood. Here, we provide functional evidence from the devastating rice blast fungus Magnaporthe oryzae that glucose can mediate TOR activity via the product of a novel carbon-responsive gene, ABL1, in order to tune cell cycle progression during infection-related development. Under nutrient-free conditions, wild type (WT) M. oryzae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 57 publications
2
79
3
Order By: Relevance
“…7A). However, it was found that treating germinating spores with glucose inhibits appressorium formation in P. oryzae strain Guy11, and the wild-type spores treated with 1% glucose only produced 30% (type II and IV) as many appressoria at 24 hpi compared with untreated spores (Marroquin-Guzman et al, 2017). We also tested appressorium formation with spore suspensions of the two strains 70-15 and Guy11 containing 1% or 2.5% glucose, and found that glucose-treated spores produced longer germ tubes, but the phenomenon of severely inhibited appressorium formation was not observed at 24 hpi (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…7A). However, it was found that treating germinating spores with glucose inhibits appressorium formation in P. oryzae strain Guy11, and the wild-type spores treated with 1% glucose only produced 30% (type II and IV) as many appressoria at 24 hpi compared with untreated spores (Marroquin-Guzman et al, 2017). We also tested appressorium formation with spore suspensions of the two strains 70-15 and Guy11 containing 1% or 2.5% glucose, and found that glucose-treated spores produced longer germ tubes, but the phenomenon of severely inhibited appressorium formation was not observed at 24 hpi (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Among the many metabolites involved, glycerol is a primary compatible solute producing turgor in appressoria (DeJong et al ., ). The proper regulation of carbohydrate and lipid metabolism, such as regulation of glucose metabolism via glucose 6‐phosphate (G6P) sensing (Wilson et al ., ; Fernandez et al ., ), glucose‐ ABL1 ‐TOR signalling (Marroquin‐Guzman et al ., ), and the carbon catabolite repression (CCR) pathway (Fernandez et al ., ), as well as the Snf1‐related lipid metabolism (Zeng et al ., ), are necessary for virulence in P. oryzae .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, studies in M. oryzae showed that the nuclear division is critical in appressorium function (Marroquin-Guzman et al, 2017). To further understand whether the deletion of MoPPE1 caused a nuclear division defect that may account for restricted invasion, a histone H1 protein fused to a red fluorescent protein (H1-RFP) construct was introduced into the wild-type strain and ΔMoppe1 mutant (Li et al, 2017a,b;Marroquin-Guzman et al, 2017).…”
Section: Moppe1 Is Required For Host Infectionmentioning
confidence: 99%
“…Previously, studies in M. oryzae showed that the nuclear division is critical in appressorium function (Marroquin-Guzman et al, 2017). To further understand whether the deletion of MoPPE1 caused a nuclear division defect that may account for restricted invasion, a histone H1 protein fused to a red fluorescent protein (H1-RFP) construct was introduced into the wild-type strain and ΔMoppe1 mutant (Li et al, 2017a,b;Marroquin-Guzman et al, 2017). However, the nuclear number were of no significant difference between the ΔMoppe1 mutant and the wild-type strains at 0, 4, 12, 24 h and infection phase when observed, suggesting that MoPpe1 may be dispensable for nuclear division which was in coordination with cell growth (Supporting Information Fig.…”
Section: Moppe1 Is Required For Host Infectionmentioning
confidence: 99%
“…Our results suggested that threonine production regulated by threonine synthase in conidia could potentially trigger conidial germination by functioning as a cellular nutrient signal. In M. oryzae , elevated levels of intracellular glucose and glutamine disturb appressorium development by activating the TOR pathway, which plays a pivotal role as an intracellular nutrient sensor [15, 38]. However, conidial germination in M. oryzae and C. orbiculare is unaffected in the presence of the TOR inhibitor rapamycin, suggesting that TOR activation is dispensable for conidial germination [15, 39].…”
Section: Discussionmentioning
confidence: 99%